Pengaruh Kombinasi Ekstrak Daun Sirsak dan PGPR (Plant Growth Promoting Rhizobacteria) Akar Bambu Apus terhadap Mortalitas Ulat Grayak pada Sawi Hijau - Dela Arsita Oktaviyani; Sonja Verra Tinneke Lumowa; Vandalita Maria Magdalena Rambitan; Nelda Anasthasia Serena (PendIPA Journal of Science Education, 2026)
The armyworm is a major pest that can reduce crop yields. Control using chemical pesticides carries the risk of causing health problems, environmental pollution, and pest resistance. Therefore, safer and more environmentally friendly alternatives in the form of botanical pesticides are needed. This study aims to determine the effect of a combination of soursop leaf extract (Annona muricata L.) and PGPR (Plant Growth Promoting Rhizobacteria) from bamboo roots (Gigantochloa apus) on the mortality of armyworms (Spodoptera litura) on green mustard plants (Brassica juncea L). The experimental design used was a randomized block design (RBD), consisting of 8 treatments and 4 replicates, resulting in 32 experimental units. The results showed that soursop leaf extract and PGPR from bamboo apus roots, at an optimal concentration of 70%, significantly increased armyworm mortality to 85%.